Assessing the reach of climate and agricultural related content via community radio stations in Senegal - Yessoufou, Adjani Nourou-Dine; Kumar, Shalander; Worou, Nadine; Faye, Aliou; Houessionon, Prosper; Huyer, Sophia; Diedhiou, Lamine; Whitbread, Anthony M. (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
The aim of the study was to evaluate the reach of AICCRA supported community radio programs in Senegal cluster intervention areas. The methodology is a combination of both quantitative and qualitative methods of data collection and analysis. It was found that the four community radio partners (Pakala FM, Jubu Jula FM, Ngaye FM, Ya Gaye FM) reached a population of around 865,385 individuals aged 15 and over, which is 75% of the potential reach. Within this population, 274,677 individuals have actually been reached by AICCRA suppoorted programs, which is 99% of the potential reach. During the last six (6) months, these community radios have been sharing through more than 95 radios shows, climate related information, climate and agricultural advisories with the ultimate aim to help smallholders take the best decision on their farm. While 76% of the population reached found the programs very useful for their activities, 20% found it of little usefulness. Many reasons have been referred to justifying how the information received through radio is useful. Among the most frequent is the fact that farmers can postpone the use of fertilizer, the weeding or other farming related activities depending on an information received about the weather conditions from the radio. The farmers also learnt through the radios how an efficient use of organic manure can increase the production yield while helping minimize the need for chemical fertilizers. As a whole, listeners suggest: more radio programs with a focus on agriculture related topics, more adaptation of existing radio programs to times where farmers are available to listen, to do shows on how to get seeds and fertilizer as this remains a central concern and challenge for farmers, to invite farmers to the shows and make sure that those who are speaking are experts, to design shows for livestock keepers on how to feed their animals and how to provide health care to these animals.